Morphological and Habitat of Parhippolyte uveae Borradaile 1900 from Tanjung Sanjangan Central Sulawesi - Retno Sari; Miswan; Muh. Rifail L. Lakoro; Suryani Musa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Parhippolyte uveae is a type of shrimp found in the Tanjung Sanjangan Tolitoli area, Central Sulawesi. The availability of red shrimp morphology and habitat data completes basic information, which is important in the sustainable management of the species. This research aims to describe the morphology and habitat of red shrimp from Tanjung Sanjangan, Tolitoli, Central Sulawesi. The sampling method uses a purposive sampling method with 5 sampling stations. The environmental parameters measured are temperature, salinity, pH, and substrate observations. The measurement results show temperatures ranging between 27.9°C -29.9°C, salinity 15-17 ppm, pH 6.29- 6.82 with coral, mud, and sand as a substrate. Morphometric data shows that the samples have a Total Length (PT) between 26-46.85 mm. Abdominal Length 18.3-30.4 mm, Carapace Length (PK) 7.5-13 mm, Carapace Width (LK) 5.25-9.5 mm, Rostrum Length (PR) 1.6-3.4 mm, Telson Length (PTel) 4.45-7.2 mm, First Abdominal Length (PabP) 1.4-2.15 mm and Second Abdominal Length (PabK) ranges from 1.8-4 mm. Meristic data shows that the Tanjung Sanjangan red shrimp has 3 upper rostrum teeth and 3-5 lower rostrum teeth, 3 pairs of dorsal spines, and 2 pairs of posterior spines. The results of these character observations are by the description of the P. uveae species.